Management Accounting Research - Lasyoud, Alhashmi Aboubaker; Awopetu, Lawrence (Journal of Accounting, Business and Management (JABM), 2024)
It is this paper’s objective to determine the concerns related to theories and methodologies that underpin the study of management accounting. The literature on management accounting includes various theories and methodologies followed by many researchers in this field of research. A review is done on prominent theories used by the management accounting field. The paper presents the frameworks utilized to classify these theories. Each theory is explained and its related criticism is presented to highlight the applicability of these theories in providing the required results when used as a base for research methodology in management accounting. The paper also reviews frameworks followed by previous studies on accounting research including Burrell and Morgan’s (1979) framework and Laughlin’s (1995) Middle-Range Thinking Approach. Although the framework by Burrell and Morgan is widely used for the classification of theories, some scholars criticized this framework. The framework developed by Laughlin (1995) is beneficial for categorizing accounting research and selecting a proper methodology for research studies in accounting. Even though Laughlin’s Middle-Range Thinking Approach has better practicality compared to the framework of Burrell and Morgan, the researchers found a limitation in his framework.